1990
DOI: 10.1111/j.1365-3059.1990.tb02526.x
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of dicarboximide‐resistant strains of Botrytis cinerea on grapevine in New Zealand

Abstract: Changes in the proportion of dicarboximide‐resistant strains of Botrytis cinerea were monitored in two vineyard trials conducted during the period from October 1985 to November 1987. Dicarboximide resistance frequency in samples taken prior to flowering from wood (dead cane‐ends, dead tendrils, old bunch remains) was high (66%) in the first trial, and low (12%) in the second trial. In treatments where resistance frequency was high on wood in spring, it decreased during the phase of disease establishment in new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The reasons for this decrease are not clear, but we interpret it as reflecting the low er fitness, specifically the lower virulence and competitive ability, of resistant strains (Pak et ai, 1990), During the phase of disease development, the application of dicarboximides leads to a progressive increase in resistance frequency, the extent of which reflects the fitness of the resistant strains. the fungicide programme applied, and disease intensity (Lorenz & Locher, 1988;Pak et <//,, 1990), If disease intensity is low, the resistance frequency will tend to increase less under a given programme than if disease intensity is high. The lower disease severity in the 1987 vintage year, compared with the 1986 year, provides an explanation as to why the resistance of plots that had only received the medium-dicarboximide programme in the 1987 year was lower than that of plots that had received the medium-dicarboximide programme for 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this decrease are not clear, but we interpret it as reflecting the low er fitness, specifically the lower virulence and competitive ability, of resistant strains (Pak et ai, 1990), During the phase of disease development, the application of dicarboximides leads to a progressive increase in resistance frequency, the extent of which reflects the fitness of the resistant strains. the fungicide programme applied, and disease intensity (Lorenz & Locher, 1988;Pak et <//,, 1990), If disease intensity is low, the resistance frequency will tend to increase less under a given programme than if disease intensity is high. The lower disease severity in the 1987 vintage year, compared with the 1986 year, provides an explanation as to why the resistance of plots that had only received the medium-dicarboximide programme in the 1987 year was lower than that of plots that had received the medium-dicarboximide programme for 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies of fungicide resistance have concentrated on changes over time, such as the demonstration that the frequency of resistant strains changed between samples within a crop season (Cohen & Samoucha, 1989; Kadish & Cohen, 1989). When extended to studies of two or more seasons, persistence of resistant strains in the field was suggested (Pommer & Lorenz, 1987; Pak et al ., 1990). Studies of the spatial pattern of resistant strains, and of disease, may provide new insights into the relative importance of pathogen dispersal mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The population of resistant isolates would be expected to decrease or remain static in the absence of field use of iprodione because the resistant isolates are less fit than the susceptible strains (Beever et al 1989). This also occurs in other B. cinerea host systems (Locher et al 1987;Pak et al 1990). Reduced field use should therefore lead to improved control by postharvest dipping.…”
Section: Discussionmentioning
confidence: 99%